Literature Review: The Potential of Tea as an Immunomodulator Through Its Antioxidant and Anti-Inflammatory Properties - Sekar Puja Alya Maharani (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
The immune system is an important mechanism to fight various pathogens. To fight pathogens, external substances are needed to improve performance and prevent pathological impacts of the immune system. Tea is one of the immunomodulatory substances that plays a role in increasing endurance because it has antioxidant and anti-inflammatory functions. This study aims to determine the potential of tea as an immunomodulator through antioxidant and anti-inflammatory mechanisms. The method used is a literature review using scientific articles that are adjusted to the inclusion criteria. Based on the results of the literature review, it shows that tea containing polyphenol compounds has an effect on reducing the levels of inflammatory cytokines such as TNF-α and IL-6 and increasing the activity of antioxidant enzymes (SOD, CAT) and reducing markers of oxidative stress.